Impact of audit committees and boards on the quality of reported earnings: A study of listed Diversified Holdings industry in Sri Lanka - Nihuma, F. (University of Jaffna, 2020)
The purpose of this study is to examine the relationship between audit committees (AC) and board of directors with earnings quality of the firms listed on diversified holdings sector, over the period 2012/13 to 2016/17 by using AC proxies, namely AC expertise, AC independence, and AC meetings and board structure variables such as board expertise, board independence, and board size. For the study, a sample of 17 companies has been selected, and Standard Jones Model (1991) has been employed for calculating discretionary accruals. Results from correlation and regression analysis suggests that measures of AC - audit meetings and board structure- board size are significantly related to earnings quality in a manner that is generally consistent with the predictions of agency theory. Furthermore, the results depicted insignificant negative impact of other AC and board characteristics on discretionary accruals, except board expertise, which had an insignificant positive impact on discretionary accruals.
Keywords: audit committee (AC); board characteristics (BOD); discretionary accruals (DACC); arnings quality